“Should i stay or should i go?”: a multiple-criteria group decision-making approach to SME internationalization - Rosário, Miguel S. M.; Ferreira, Fernando A. F.; Çipi, Amali; Pérez-Bustamante Ilander, Guillermo O.; Banaitienė, Nerija (Technological and Economic Development of Economy, 2021)
Due to domestic markets’ current economic conditions, companies increasingly feel that they need to become actively involved in international trade. However, small and medium-sized enterprises (SMEs) typically face financial and intellectual constraints during internationalization processes. This means that decision makers must consider a wide range of different variables before deciding to internationalize firms. This study sought to integrate a well-established problem structuring method (i.e., cognitive mapping) and a multiple-criteria decision analysis (MCDA) technique (i.e., Decision EXpert (DEX)) in order to develop a decision model suitable for the identification and assessment of variables influencing SME internationalization capability. Using data collected during face-to-face meetings with a panel of experts (i.e., SME entrepreneurs and chief executive officers (CEOs)), a constructivist method of evaluating SME internationalization capability was created and tested using real data. The results confirm that the dual methodology adopted facilitates the development of a robust evaluation model that can improve decisionmaking processes in the context in question. Specifically, the proposed model identifies product features as the most important factor in SME capability for successful internationalization. In addition, internal factors are significantly more relevant than external factors. The integrated use of cognitive mapping and DEX provides decision makers with a well-informed perspective on SME internationalization capability. We know of no prior research reporting the use of these two methodologies in the SME internationalization context.